Peran Motivasi Dalam Lingkungan Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Kantor Jasa Akuntan - Zulfa Sabina; Laylan Syafina (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to analyze the role of motivation in the work environment and discipline on employee performance in accounting services firms. Qualitative methods are used to gain in-depth insight into how motivation and work discipline influence employee performance. Data was collected through interviews with employees at different accounting services offices. The research results show that high motivation and a conducive work environment can improve employee performance, while a lack of work discipline can hinder employee performance. Through this research, it is hoped that it can provide a better understanding of the factors that influence employee performance in the context of accounting services firms.